2019
DOI: 10.3390/biom9110663
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Action and Interactions between Thyroid Peroxidase and Lipoxygenase Inhibitors Derived from Plant Sources

Abstract: This study focused on the effect of kaempferol, catechin, apigenin, sinapinic acid, and extracts from plants (i.e., parsley, cumin, mustard, green tea, and green coffee) on thyroid peroxidase (TPO) and lipoxygenase (LOX) activity, antiradical potential, as well as the result of interactions among them. Catechin, sinapinic acid, and kaempferol acted as a competitive TPO inhibitors, while apigenin demonstrated an uncompetitive mode of inhibitory action. Ethanol extracts from all plants acted as competitive TPO i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Luteolin is one of the most common flavones with antioxidant, anticancer, antiinflammatory, and antiapoptotic properties in TCMSP (De Stefano et al, 2021). A previous study also suggests that kaempferol is a potential bioaccessible TPO activator based on effective LOX inhibitors, further indicating potentially healthpromoting effects for HT (Habza-Kowalska et al, 2019). Some studies have also shown that luteolin's mechanisms showed potent anti-inflammatory activity, including the activation of NF-κB, which leads to the expression of IL-6 and COX-2 (Xagorari et al, 2001;Ching-Chow et al, 2004).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Luteolin is one of the most common flavones with antioxidant, anticancer, antiinflammatory, and antiapoptotic properties in TCMSP (De Stefano et al, 2021). A previous study also suggests that kaempferol is a potential bioaccessible TPO activator based on effective LOX inhibitors, further indicating potentially healthpromoting effects for HT (Habza-Kowalska et al, 2019). Some studies have also shown that luteolin's mechanisms showed potent anti-inflammatory activity, including the activation of NF-κB, which leads to the expression of IL-6 and COX-2 (Xagorari et al, 2001;Ching-Chow et al, 2004).…”
Section: Discussionmentioning
confidence: 94%
“…In the study, eleven main active components were screened of PV: luteolin, quercetin, beta-sitosterol, kaempferol, stigmasterol, morin, spinasterol, delphinidin, vulgaxanthin-I, poriferasterol monoglucoside_qt, and stigmast-7-enol. Molecular docking showed that the active ingredients, including luteolin and kaempferol, had a good affinity for the hub disease proteins in clinical therapeutics (Xia et al, 2016;Habza-Kowalska et al, 2019). The results demonstrated that luteolin has a strong affinity for disease proteins of HT, and quercetin had a strong affinity for serum thyroid peroxidase (TPO).…”
Section: Discussionmentioning
confidence: 99%
“…Sinapinic acid, catechin, and kaempferol were competitive TPO inhibitors, while apigenin was an uncompetitive TPO inhibitor. The highest radical scavengers belonged to sinapinic acid, catechin, and compounds derived from mustard and green coffee [ 93 ].…”
Section: The Role Of Tpo and Lox In Thyroid Oxidative Stress And Modu...mentioning
confidence: 99%
“…Inflammation and oxidative stress are closely connected pathways. Thyroid hormones act as antioxidant balancers, while both hyperthyroidism and hypothyroidism have been determined to be linked with oxidative stress [ 93 , 97 ]. Plants are major sources of antioxidant polyphenols with proven biological effects.…”
Section: The Role Of Tpo and Lox In Thyroid Oxidative Stress And Modu...mentioning
confidence: 99%
“…The CI values are presented in Table 5. Our previous studies used this method on pure polyphenolic compounds and plant extracts against TPO and LOX [4,24]. Studies [7] showed the synergistic action of ferulic and chlorogenic acids as LOX inhibitors.…”
Section: Strong Synergism Synergismmentioning
confidence: 99%